2023
DOI: 10.3390/healthcare11233096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of UV-C Radiation in Eliminating Microorganisms of Special Epidemiological Importance from Touch Surfaces under Laboratory Conditions and in the Hospital Environment

Anna Różańska,
Monika Walkowicz,
Małgorzata Bulanda
et al.

Abstract: Introduction: Healthcare-associated infections in the post-pandemic era are as important as they were before COVID-19. The dominant route of transmission of microorganisms in health care units is the contact route, for which hand hygiene is of cardinal importance, but also effective disinfection of touch surfaces. Traditional disinfection based on chemical compounds is sensitive to human errors. Therefore, a valuable supplement to it can be contactless disinfection methods, including the use of UV-C. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…above 60% of the initial number of exposed colonies/plaques) was usually visible on the glass and plastic surfaces. The results obtained confirm the observations of Gidari et al [13] regarding the survivability of SARS-CoV-2 virus, Pedrós-Garrido et al [18] with respect to Pseudomonas fluorescens, and Różańska et al [19], regarding S. aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Enterobacter cloacae, Enterococcus faecalis, P. aeruginosa, and Candida auris deposited on plastic surfaces. The lastmentioned researchers studying the efficacy of UV-C radiation in eliminating the microorganisms from frequently touched plastic, glass, and steel surfaces, revealed that the surface material plays a crucial role in the effectiveness of UV-C disinfection, indicating the need for surface-specific disinfection strategies in a given environment.…”
Section: Discussionsupporting
confidence: 88%
“…above 60% of the initial number of exposed colonies/plaques) was usually visible on the glass and plastic surfaces. The results obtained confirm the observations of Gidari et al [13] regarding the survivability of SARS-CoV-2 virus, Pedrós-Garrido et al [18] with respect to Pseudomonas fluorescens, and Różańska et al [19], regarding S. aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Enterobacter cloacae, Enterococcus faecalis, P. aeruginosa, and Candida auris deposited on plastic surfaces. The lastmentioned researchers studying the efficacy of UV-C radiation in eliminating the microorganisms from frequently touched plastic, glass, and steel surfaces, revealed that the surface material plays a crucial role in the effectiveness of UV-C disinfection, indicating the need for surface-specific disinfection strategies in a given environment.…”
Section: Discussionsupporting
confidence: 88%
“…No-touch disinfection includes Ultraviolet C light emitting diodes (UVC LED) disinfection or vaporized hydrogen peroxide systems used for terminal cleaning and disinfection procedures [27]. UVC technology is a validated disinfection modality for water, air, and surface applications, and the UVC spectrum (200 -280 nm) offers enhanced germicidal disinfection when used in conjunction with common chemical cleaning agents [28][29][30][31][32][33][34][35]. UVC LED technology can inactivate microbes and pathogens because the intracellular structures, like DNA/RNA and proteins, are susceptible to the specific density of UVC photons that are emitted in a controlled environment, causing critical genomic damage that mainly occurs through a disruption in the adenine-to-thymine bond, resulting in a pyrimidine dimer between the adenines.…”
Section: Uvc Led Technologymentioning
confidence: 99%
“…Clinical pilot testing designed to mimic common surfaces in a hospital setting (i.e., steel, plastic, glass) also found UVC technology to be effective at disinfecting after 10 minutes of exposure; however, effectiveness was statistically different across all three surfaces. While this pilot study was conducted in a clinical environment, only four patient rooms with random swab testing were used in the experiment at a time without any known outbreaks [32]. The Tru-D (Lumalier, Memphis, TN) UVC room disinfection device was clinically tested in an acute-care tertiary hospital in Chapel Hill, North Carolina.…”
Section: Surfacementioning
confidence: 99%